Understanding the Assembly of an Artificial Protein Nanotube. Issue 24 (2nd November 2016) - Nagano, Soshichiro; Banwell, Eleanor F.; Iwasaki, Kenji; Michalak, Maciej; Pałka, Renata; Zhang, Kam Y. J.; Voet, Arnout R. D.; Heddle, Jonathan G.
Abstract : TRAP (trp RNA‐binding attenuation protein) is a stable, ring‐shaped protein that has proven useful in the development of artificial, self‐assembled biological structures including a protein nanotube that assembles from a cysteine‐containing mutant. While the structure of the nanotube is known in some detail, the nature of the interactions that connect the protein rings together to form tubes is not known. Here, evidence is presented that the two faces of the ring bind together using mixed interactions: On one face cysteine side chains are linked to the same face of a corresponding ring via a dithio linker molecule while the other face does not require covalent interactions and can assemble using protein–protein interactions alone. A coherent 3D model is constructed to explain the observed results, which are ultimately due to specific structural features that modulate the types of bonding that can occur. This detailed understanding offers the prospect of engineering the TRAP nanotube to endow it with bespoke properties. Abstract : The ring shaped trp RNA‐binding attenuation protein, when modified, is known to stack to form nanotubes in the presence of dithiol linkers but the details of how the faces interact are not fully understood. New work combining biochemical experiments with in silico modeling has shed new light on the surprisingly complex protein interfaces in these nanotubes.